Sulfonyl Nitrene and Amidyl Radical: Structure and Reactivity - Zelenka, Jan; Pereverzev, Aleksandr; Jahn, Ullrich; Roithová, Jana (Chemistry (Weinheim an der Bergstrasse, Germany), 2022)
Photocatalytic generation of nitrenes and radicals can be used to tune or even control their reactivity. Photocatalytic activation of sulfonyl azides leads to the elimination of N2 and the resulting reactive species initiate C-H activations and amide formation reactions. Here, we present reactive radicals that are generated from sulfonyl azides: sulfonyl nitrene radical anion, sulfonyl nitrene and sulfonyl amidyl radical, and test their gas phase reactivity in C-H activation reactions. The sulfonyl nitrene radical anion is the least reactive and its reactivity is governed by the proton coupled electron transfer mechanism. In contrast, sulfonyl nitrene and sulfonyl amidyl radicals react via hydrogen atom transfer pathways. These reactivities and detailed characterization of the radicals with vibrational spectroscopy and with DFT calculations provide information necessary for taking control over the reactivity of these intermediates.
Keywords: transport elektronů; ion spectroscopy; reaction mechanisms; azidy; nitrene; amidyl radical; Imines; protony; iminy; Protons; Electron Transport; photocatalysis; Azides; Hydrogen; vodík